2/3x-2=6+11/12x

Simple and best practice solution for 2/3x-2=6+11/12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3x-2=6+11/12x equation:



2/3x-2=6+11/12x
We move all terms to the left:
2/3x-2-(6+11/12x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 12x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
2/3x-(11/12x+6)-2=0
We get rid of parentheses
2/3x-11/12x-6-2=0
We calculate fractions
24x/36x^2+(-33x)/36x^2-6-2=0
We add all the numbers together, and all the variables
24x/36x^2+(-33x)/36x^2-8=0
We multiply all the terms by the denominator
24x+(-33x)-8*36x^2=0
Wy multiply elements
-288x^2+24x+(-33x)=0
We get rid of parentheses
-288x^2+24x-33x=0
We add all the numbers together, and all the variables
-288x^2-9x=0
a = -288; b = -9; c = 0;
Δ = b2-4ac
Δ = -92-4·(-288)·0
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{81}=9$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-9}{2*-288}=\frac{0}{-576} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+9}{2*-288}=\frac{18}{-576} =-1/32 $

See similar equations:

| 1/3x=45* | | 5h-5=25 | | 39=6h-9 | | -15+3x17x=-43 | | 65,000=10,000(1.06)3x | | 10+7w=5w-10 | | 10−a=8 | | v+13/5=8 | | 14=5u-6 | | 96=20+4x4 | | 56.52=(3.14r)2 | | 10 − a= 8 | | 3x+2/x-5=2 | | 20+7d=-20+9d | | 0,70+3.80+3x+2x=50 | | x+(x+2)+(x+4)=6 | | d-48/7=7 | | 5x-9=7x+12 | | -8(-3m-3)=-69 | | -4(v+3)=-12-14v | | -7h+10=-5h-10 | | -68-9x=-5(8x-5) | | 2=17-5c | | 2.54(x+4)=17.78 | | 10^(x-7)=10000 | | 2z+4/5*5=z-1*5 | | 74=7q-3 | | -8(-3m-3)=-9 | | 32=2u+18 | | 8=-3/4h | | 310=−6.2ff= | | 2.47(x-6)=4.94 |

Equations solver categories